THE CIVILIZATIONAL SIGNIFICANCE OF THE DEVELOPMENT OF SCIENCE IN THE TIMURID PERIOD (American Journal of Research in Humanities and Social Sciences, 2026)
This article examines the scientific, cultural, and civilizational significance of the Timurid era and analyzes its study in modern historiography. Special attention is given to the role of Amir Temur and his successors in promoting science, education, architecture, and state administration throughout Central Asia. The research highlights the development of major scientific centers such as Samarkand, Bukhara, and Herat, as well as the contributions of outstanding scholars including Mirzo Ulugbek, Qozizoda Rumi, Ghiyath al-Din al-Kashi, and Ali Qushji. The study investigates the importance of historical sources, particularly the works of Sharafuddin Ali Yazdi, Nizamiddin Shami, and Ibn Arabshah, in understanding the political, cultural, and intellectual achievements of the Timurid period. Furthermore, it evaluates the transformation of Timurid studies during the years of Uzbekistan’s independence, emphasizing new methodological approaches and the growing interest in the Timurid legacy at both national and international levels. The findings demonstrate that the Timurid era played a crucial role in preserving and advancing the traditions of the Eastern Renaissance and made a lasting contribution to world civilization.